Communication-as-Control: Intent-Aware Interaction for Scalable Multi-Agent Coordination - Imani, Mahdi; Lan, Tian (Proceedings of the AAAI Symposium Series, 2026)
Uncrewed Aerial Systems (UAS) increasingly operate as large, heterogeneous teams under partial observability. In such settings, coordination depends on how agents infer, represent, and act upon uncertainty about one another: belief divergence is a natural consequence of asymmetric sensing and latent intent, and naive communication mechanisms do not scale with team size. We argue for a reframing of interaction as communication-as-control, grounded in a small set of tightly coupled capabilities that link sensing to distributed execution under interaction constraints. Rather than prescribing a fixed pipeline, coordination in such teams relies on several interdependent capabilities. First, agents must perform implicit intent inference without communication, forming uncertainty-aware beliefs over teammate intent and progress from observable behavior. Second, such uncertainty can inform selective explicit interaction, with targeted, minimal exchanges invoked only when unresolved ambiguity becomes consequential for joint decision-making. Third, uncertainty arising from both implicit inference and explicit interaction can be leveraged to support belief-guided coordination and adaptation when alignment is partial, delayed, or unattainable. This makes selective interaction a scalability mechanism: as teams grow in size and heterogeneity, coordination remains feasible only if communication is sparse, recipient-specific, and tied to decision relevance.